PENGARUH PENERAPAN E-BILLING SYSTEM TERHADAP KEPATUHAN PEMBAYARAN PAJAK PPh FINAL WAJIB PAJAK UKM DI KABUPATEN SINJAI - Nasrullah Nasrullah; Sri Andayaningsih; Sultan Sarda; Wiwied Ahriani Pratiwi (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to determine the effect of E-Billing on Taxpayer Compliance in Sinjai Regency. This study uses quantitative methods. The population in this study is MSME Taxpayers at the Sinjai Tax Counseling and Consultation Service Office as many as 8824 Taxpayers. The sampling technique used is Random Simplification, so that a sample of 99 taxpayers is obtained, with the determination of the sample based on an error rate of 10% developed by the slovin formula. The analysis technique used in this study uses an interactive model with respondents where the respondent's interpretation data is then regulated by using data analysis techniques in this case SPSS. Based on the results of data analysis carried out, the application of E-Billing has an effect on Taxpayer Compliance in Sinjai Regency. This shows that taxpayers will be obedient in making tax payments if the application of e-billing is good, application of good e-billing can be the main capital and is an important thing to be able to attract the attention of taxpayers. This shows that the better the implementation provided by E-Billing, the higher the Taxpayer Compliance, thus the hypothesis is accepted.